2019
DOI: 10.1002/cam4.1952
|View full text |Cite
|
Sign up to set email alerts
|

The cancer incidence and mortality among children and adolescents during the period of 2010‐2014 in Henan Province, China

Abstract: Objective The cancer etiology in children and adolescents is largely different with that in adults, and the description in epidemiology still remains deficiency. Therefore, we described the cancer incidence and related epidemiological features in children and adolescents to provide clues for etiological studies. Methods Cancer incidence stratified by age, gender, and areas was calculated using data extracted from population‐based cancer registries in Henan Province, China. All cancer among children aged 0‐19 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…1 It was estimated that the total number of new cases diagnosed with lung cancer in People's Republic of China in 2015 was about 787,000, corresponding to over 2100 new lung cancer cases diagnosed each day. 2 Surgical resection remains the mainstay of treatment for early-stage NSCLC; however, most patients relapse after operation, which is considered to be associated with "residual tumor cells," 3,4 or "tumor micrometastasis." 5,6 Therefore, 5-year survival rates remain at approximately 50% for stage IA and 20% for stage III NSCLC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It was estimated that the total number of new cases diagnosed with lung cancer in People's Republic of China in 2015 was about 787,000, corresponding to over 2100 new lung cancer cases diagnosed each day. 2 Surgical resection remains the mainstay of treatment for early-stage NSCLC; however, most patients relapse after operation, which is considered to be associated with "residual tumor cells," 3,4 or "tumor micrometastasis." 5,6 Therefore, 5-year survival rates remain at approximately 50% for stage IA and 20% for stage III NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Therefore, 5-year survival rates remain at approximately 50% for stage IA and 20% for stage III NSCLC. 7 Neoadjuvant therapy is an accepted practice in patients with resectable NSCLC for several advantages: (1) reducing tumor burden before operation; (2) directing adjuvant therapy on the basis of patients' response to neoadjuvant treatment; and (3) using pathologic remission as a surrogate end point for survival benefit. Several studies have reported that neoadjuvant chemotherapy provides benefit compared with operation alone.…”
Section: Introductionmentioning
confidence: 99%
“…The subjects included in our study were extracted from the database of Linzhou Cancer Registry, which is one of the earliest Cancer Registries in China and was established in the 1960s. The procedures of data collection, standards of cancer cases coding, and the validity check of cancer cases were conducted according to the criteria of “International Agency for Research on Cancer/International Association of Cancer Registries (IARC/IACR)” and “Guideline for Chinese Cancer Registration.” The cancer cases were sourced using records of hospitals, health insurance system, new rural cooperative medical systems, and vital statistical systems . The quality control procedures had been described previously, they would be summarized then as follows .…”
Section: Methodsmentioning
confidence: 99%
“…The procedures of data collection, standards of cancer cases coding, and the validity check of cancer cases were conducted according to the criteria of “International Agency for Research on Cancer/International Association of Cancer Registries (IARC/IACR)” and “Guideline for Chinese Cancer Registration.” The cancer cases were sourced using records of hospitals, health insurance system, new rural cooperative medical systems, and vital statistical systems . The quality control procedures had been described previously, they would be summarized then as follows . The quality control indices of the Linzhou cancer registration data including comparability, validity, and completeness were evaluated by the IARC/IACR and the National Central Cancer Registry of China (NCCR).…”
Section: Methodsmentioning
confidence: 99%
“…2,[4][5][6] These advances in treatment have also increased the 5-year relative survival rates of patients, reaching to around 85% in developed countries and 70.5% to 80% in China. 1,7,8 Due to the prolonged length of stay in hospitals and the need for specialized facilities and care, children and adolescents with pediatric cancer require a significantly greater amount of healthcare resources than patients with other pediatric health conditions. 9,10 Aside from medical bills such as diagnostic tests, chemotherapy, and hospitalization, the financial costs for treating pediatric cancer also include hidden non-medical expenses, such as transport, accommodation, and loss of parental income.…”
Section: Introductionmentioning
confidence: 99%